DISCOURSE ANALYSIS ON ADVERTISEMENT - Sukrisno, Alim (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2010)
This article is concerned with the analysis of discourse on advertisement. The aim of this discussion is to try to make sense of an advertisement from the point of view of linguistic construction, meaning, and its textuality. Results of the discussion indicate that in order to be called a text the observed advertisement should be analyzed by means of elliptical operation. As soon as the elliptical clauses and sentences of the advertisement are established, the meaning or intention of the advertisement can be derived. Unless the truths of the messages conveyed by the advertisement are clarified, ambiguities will still remain that will affect the understanding and response of the readers or potential buyers. As a material for discourse analysis, however, the advertisement is a very interesting thing to be talked about. ÃÂ Key words: advertisement, ellyptical, ambiguity